Distribusi Headway Lalu Lintas Kendaraan Pada Jalan Yang Curam Dengan Tikungan Tajam Di Silaing Bawah Kota Padang Panjang - Rival, Muhammad; Purnawan, Purnawan (Universitas Andalas, 2024)
On the road section between Padang City and Padang Panjang City, the geometric conditions of the road are steep and winding, making it difficult for drivers when they are in a convoy of vehicles, thus allowing accidents to occur. Therefore, a headway value is needed to control the safe distance between vehicles so that there are no collisions between vehicles when convoying. This study aims to determine the distribution of traffic headway on steep roads with sharp bends. The study took traffic flow data at 2 observation posts on the Sutan Syahrir, Silaing Bawah road section. Primary data collection was carried out using a camera. Data processing used Avidemux and Microsoft Excel software. To obtain the best distribution model on steep roads with sharp bends, a Kolmogorov-Smirnov test was carried out using EasyFit Professional software. Based on the data analysis, the following results were obtained: Based on the z test, the results of the analysis of downhill and uphill flows on the first and second days of observation can be concluded that the headway of the vehicle population at Post I and Post II has the same population headway. The best distribution model (goodness of fit) from the results of the time headway test for Saturday at the first post is the Johnson SB model and Gen. Extreme Value on the incline. Then at the second observation post the best distribution model obtained was Pert on the descent, while on the ascent the Johnson SB distribution model was obtained. For the distribution model on Sunday, at the first post the Johnson SB model was obtained for the descent, and the Wakeby model on the ascent. Then at the second post the Power Function distribution model was obtained on the descent, and the Wakeby model on the ascent.